DIGITALIZATION OF WEB-BASED MOBILE PHONE ACCESSORIES SALES AT DZMOON STORE - Novalinda Masihani Ndruru; Puji Chairu Sabila; Nurul Afni; Fricles Ariwisanto Sianturi; Taufik Ismail Simanjuntak (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
Dzmoon Store is a business that sells mobile phone accessories. The challenges faced include requiring customers to visit the store in person to obtain product and stock information, product promotions not yet reaching customers outside the region, online ordering not yet available, and ineffective sales report processing. This research aims to develop a web-based mobile phone accessory sales information system that can facilitate customer product information access, online ordering, and sales data management. The waterfall method used consists of analysis, design, implementation, testing, and maintenance. Data collection was conducted through observations and interviews at Dzmoon Store. The system was designed using Unified Modeling Language (UML) and implemented using PHP and MySQL. The results show that the system is capable of providing online product and stock information, facilitating website purchase transactions, and generating sales reports stored in a database. Testing results indicate that the login, data management, data search, and report printing functions operate according to user requirements. Therefore, the developed web-based sales system can improve the ease, speed, and effectiveness of the sales process and data management at Dzmoon Store.